2021
DOI: 10.1161/circheartfailure.120.007347
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Impact of Systolic Blood Pressure and Perfusion Status on Mortality in Acute Heart Failure

Abstract: Background: Physical examination remains the cornerstone in the assessment of acute heart failure. There is a lack of adequately powered studies assessing the combined impact of both systolic blood pressure (SBP) and hypoperfusion on short-term mortality. Methods: Patients with acute heart failure from 41 Spanish emergency departments were recruited consecutively in 3 time periods between 2011 and 2016. Logistic regression models were used to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Indeed, many cases of acute pulmonary oedema are usually associated with systemic hypoperfusion and hypertensive crisis, as our data also suggest: median SBP on patients treated with IV-NTG was 153 mmHg (IQR, 135–178), with similar values in treated patients that exhibited severe clinical hypoperfusion (157 mmHg; IQR, 131–186). A recent study described that hypoperfusion confers an incremental risk of 30-day all-cause mortality not only in patients with low SBP but also in normotensive patients [19]. Therefore, this finding could, to some extent, be linked to this fact.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, many cases of acute pulmonary oedema are usually associated with systemic hypoperfusion and hypertensive crisis, as our data also suggest: median SBP on patients treated with IV-NTG was 153 mmHg (IQR, 135–178), with similar values in treated patients that exhibited severe clinical hypoperfusion (157 mmHg; IQR, 131–186). A recent study described that hypoperfusion confers an incremental risk of 30-day all-cause mortality not only in patients with low SBP but also in normotensive patients [19]. Therefore, this finding could, to some extent, be linked to this fact.…”
Section: Discussionmentioning
confidence: 98%
“…Most clinical investigations have used 90 mmHg for systolic BP (SBP) and 60 mmHg for mean arterial pressure (MAP) for at least 30 minutes. Concomitant presence of hypoperfusion is required, assessed by exam 38 or simple measures of hypoperfusion, such as decreased urine output or increased lactate. It should be recognized that tissue hypoperfusion can be present without hypotension if CO has significantly fallen but endogenous vasoconstrictor responses are maintaining BP.…”
Section: Cardiogenic Shockmentioning
confidence: 99%
“…A study on 41 Spanish emergency departments among 10,979 patients suffering from acute heart failure demonstrated that 30-day mortality was negatively correlated with initial SBP. After adjustment for the risk factors, the prognostic impacts of hypo-perfusion on 30-day mortality varied across SBP categories ( Rossello et al, 2021 ). Another clinical trial also indicated that SBP may be more related to patients’ tissue perfusion and outcomes perioperatively ( Futier et al, 2017 ).…”
Section: The Relationship Between Sbp and Comentioning
confidence: 99%